PERAN BUDAYA LITERASI DALAM MENINGKATKAN MINAT BACA PESERTA DIDIK DI SEKOLAH DASAR - Rokmana Rokmana; Endah Noor Fitri; Dian Fixri Andini; Misnawati Misnawati; Alifiah Nurachmana; Ibnu Yustiya Ramadhan; Syarah Veniaty (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine the role of literacy activities, obstacles, and efforts made by schools in increasing elementary school students' interest in reading. This research is a descriptive qualitative research with the research subjects being the principal, teachers and students of grade 5 SD Islam Terpadu Al Ghazali Palangka Raya. Data collection techniques through interviews, observation and documentation. Data analysis techniques include data collection, data reduction, data display, and conclusions. Based on the data obtained, it shows that: (1) The literacy culture applied in schools plays an important role in students' interest in reading, (2) The lack of infrastructure owned by schools is an obstacle in literacy activities.